Peningkatan Pengetahuan dan Sikap Siswa SDN 146/IV Kota Jambi tentang PHBS Indikator Cuci Tangan Pakai Sabun Melalui Media Ular Tangga - Syaridayanti, Yulti; Sari, Puspita; Rahayu Ningsih, Vinna (UI Scholars Hub, 2025)
Background. The lack of knowledge and attitudes among students regarding the PHBS indicator of handwashing with soap in schools can lead to various health problems, therefore, it is necessary to use engaging media such as snakes and ladders to educate students. Objective. To determine how the snake and ladder media affects the knowledge and attitudes of SDN 146/IV Kota Jambi students regarding PHBS indicators of handwashing with soap. Method. Quantitative research with a pre-experimental method of one group pre and post-test design. The treatment was in the form of health education intervention using snakes and ladders media. The questionnaire was used as a data collection tool and was carried out on October 7, 2024. The research subjects were 32 people. The sample was selected using the pro-portional stratified random sampling method. Data were analyzed using the Wilcoxon statistical test. Result. The pretest results show that the average student knowledge score increased from 9.69 in the pretest to 12.53 in the posttest, and the attitude score increased from 46.06 in the pretest to 56.41 in the posttest. There is an influence of the snake and ladder game on the improvement of knowledge and attitudes of students at SDN 146/IV Kota Jambi with a P-Value of 0.001. Future researchers are expected to provide interventions using snakes and ladders with interactive learning through singing.